2004
DOI: 10.2298/jmh0402149n
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intracerebroventricularly administered octreotide on gonadotrophic cells in female rats

Abstract: Effects of intracerbroventricularly (ICV) administered octreotide on gonadotrophic cells (FSH and LH) of adult Wistar female rats were examined by immunocytochemical and morphometric methods. The animals received ICV three 1.0 mg doses of octreotide dissolved in 10 mL saline every second day. The controls were treated with equivalent volume of physiological saline by the same schedule. FSH-and LH-producing cells were examined using peroxidase-antiperoxidase immunocytochemical procedure. Morphometric and stereo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…For example, an impaired somatotropic axis negatively affects reproduction. Somatostatin treatment inhibits pituitary gonadotropic cells and initial folliculogenesis in the ovaries of infant, peripubertal and adult females [252][253][254][255][256][257]. Polycystic ovary syndrome (PCOS) is of great importance, owing to its prevalence in up to 10% of the women population of reproductive age.…”
Section: Programming Of Hipothalamic-pituitary-gonadal Axismentioning
confidence: 99%
“…For example, an impaired somatotropic axis negatively affects reproduction. Somatostatin treatment inhibits pituitary gonadotropic cells and initial folliculogenesis in the ovaries of infant, peripubertal and adult females [252][253][254][255][256][257]. Polycystic ovary syndrome (PCOS) is of great importance, owing to its prevalence in up to 10% of the women population of reproductive age.…”
Section: Programming Of Hipothalamic-pituitary-gonadal Axismentioning
confidence: 99%
“…Ben-Shlomo and Melmed (2010) suggested that this effect is probably mediated through induction of cell apoptosis or induction of cell senescence, rather than inhibition of mitogenesis. Indeed, pycnotic gonadotropic cells were observed after acute central octreotide administration (Nestorović et al 2004b). …”
Section: Discussionmentioning
confidence: 99%
“…(Estupina et al, 1996, Zorrila et al, , 1991. Central injections with SOM or a SOM analog (octreotide) decreased the number of gonadotropic cells in the pituitary (Lovren et al, 1998;Nestorovic et al 2002;. Also, we previously showed that a single central injection with octreotide significantly attenuated the E 2 -induced Luteinizing Hormone (LH) surge and significantly decreased the activation of Gonadotropin Releasing Hormone (GnRH) cells in the hypothalamus of female rats (van Vugt et al, 2004).…”
Section: Introductionmentioning
confidence: 96%